2009
DOI: 10.1002/ejoc.200900530
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses of Triostin A Antibiotic and Nucleobase‐Functionalized Analogs as New DNA Binders

Abstract: A total synthesis of the natural product triostin A, wherein the N-methylated depsipeptide scaffold is constructed by solution-phase peptide chemistry followed by disulfide formation and macrocyclization, is described. Finally, the quinoxalines were attached to provide the DNA bisintercalator. Analogs of triostin A were obtained by the successive functionalization of the cyclic depsipeptide with pyrimidine or purine recognition units. The attachment of functional units

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…Replacing of quinoxaline intercalating units by different nucleobases led to a wide family of rigid nucleobase-depsipeptide bicyclic conjugates 9 (Fig. 6, up) [34][35][36]. Conjugates were investigated for their DNA-binding potential and for selectivity to the DNA-abasic site.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Replacing of quinoxaline intercalating units by different nucleobases led to a wide family of rigid nucleobase-depsipeptide bicyclic conjugates 9 (Fig. 6, up) [34][35][36]. Conjugates were investigated for their DNA-binding potential and for selectivity to the DNA-abasic site.…”
mentioning
confidence: 99%
“…Conjugates were investigated for their DNA-binding potential and for selectivity to the DNA-abasic site. Although experiments indicated that mode of conjugate binding differed from that of triostin A bisintercalation, none of the conjugates 9 showed favored recognition of abasic sites [36]. Another modification of triostin A comprised replacement of quinoxalines by adenine and thymine combined by additional functionalization with a metal binding moiety [37] (Fig.…”
mentioning
confidence: 99%